Evaluating the effects of mindfulness-based interventions for informal palliative caregivers: A systematic literature review. (February 2016) - Jaffray, Linda; Bridgman, Heather; Stephens, Miranda; Skinner, Timothy
Background: There is a need to identify proactive, evidence-based interventions to support informal palliative caregivers. Mindfulness-based interventions, evidenced in the literature as providing physical and mental health benefits for diverse populations, may have application in the setting of palliative caregiving. Aim: To describe, evaluate and synthesise the peer-reviewed literature on the effects of mindfulness-based interventions for informal palliative caregivers. Design: A Systematic Literature Review according to the Preferred Reporting Items for Systematic Review and Meta Analyses guidelines and a Narrative synthesis. Data sources: The Cochrane Library, CINAHL, MEDLINE, PsycINFO and EMBASE databases, searched from inception to February 2014 and references of included studies. Results: A total of 13 articles, reporting 10 studies ( n = 432 participants) were included. All studies were conducted in the last 5 years. Dementia caregivers were the most frequently researched population ( n = 7). Results suggest that mindfulness-based interventions are feasible and acceptable to offer to informal palliative caregivers and may provide benefit, particularly in terms of reducing depression and caregiver burden and increasing quality of life. However, effects were not as robust as findings in the wider mindfulness intervention literature. Conclusion: This is the first systematic literature review on this topic. Results suggest both feasibility and potential benefit. Further qualitative research is required to explore the outcomes identified by informal caregivers themselves as the reduced magnitude of effect may suggest that we are not measuring the right outcomes in this context. This would inform more sensitive outcome measures for future intervention studies and guide the development and application of mindfulness-based models in this area.